Bioactive constituents from the leaves of Melastoma Malabathricum L - Darnis, Deny Susanti; Mohd. Sirat, Hasnah; Ahmad, Farediah; Mat Ali, Rasadah (Universitas Islam Indonesia, 2008)
Phytochemical and bioactivity studies of the leaves of Melastoma malabathricum L. (Melastomataceae) have been investigated. The n-hexane extract yielded α-amyrin, patriscabatrine and auranamide, ethyl acetate extract gave quercetin and quercitrin, and methanol extract gave quercitrin and kaempferol-3-O-(2”,6”-di-O-p-trans-coumaroyl)glucoside. The crude extracts and isolated compounds were screened for their antioxidant and cytotoxic activities. The antioxidant assay was carried out by FTC and DPPH radical scavenging method. Kaempferol-3-O-(2”,6”-di-Op- trans-coumaroyl)-glucoside, quercetin and quercitrin showed strong activities with inhibition more than 90% in the FTC method. Quercetin was found to be the most active as radical scavenger in DPPH method with IC50 of 0.69 µM. α-Amyrin and kaempferol-3-O-(2”,6”-di-O-p-transcoumaroyl) glucoside demonstrated the strongest activities in the anti-inflammatory assay of TPA mouse ear oedema with IC50 of 0.11 and 0.34 mM/ear, respectively.